Crystalline rice husk silica reinforced AA7075 aluminium chips by cold compaction method. Issue 10 (13th October 2021) - Latif, N.A.; Mohd Joharudin, N.F.; Mustapa, M.S.; Hao, S.W.; Supawi, A.; Hassan, N.Z.; Noranai, Z.
Abstract: Aluminium matrix composite is highly demanded in various industries due to its low density and good mechanical properties as most commonly studied for metal matrix composite. The properties of the composite be improved with the addition of reinforcement significantly such as silicon carbide, aluminium oxide, and boron carbide that can be mixed easily to metal matrix composite. The study of crystalline rice husk silica reinforced AA7075 aluminium chips on mechanical properties were investigated. The rice husk ash was burned at 1200 °C and it was characterized in the crystalline phase by conducting x‐ray diffraction test. The mechanical properties of aluminium matrix composite were obtained by microhardness and compression tests. Results of mechanical properties for the addition of rice husk silica up to 7.5 wt.% composition of crystalline rice husk silica showed increase value of microhardness and compression strength which are the highest value of 75.94 HV 0.1 and 443 MPa, respectively compared to another aluminium matrix composite. Hence, based on investigation to crystalline rice husk silica reinforced aluminium, it has good potential to improve the mechanical properties of aluminium matrix composite which were dependent to the composition of crystalline rice husk silica reinforcement in aluminium matrix composite. Abstract : Direct conversion has emerged as a potential alternative to the conventional remelting and recycling technique. Owing to the high energy requirement for melt and cast aluminium, this study employed recycling concept by utilizing cold compaction process. Recycling industrial wastes promises low production cost, environmentally friendly and saving primary aluminium resources.